Design Of The Special / Special For Inclusion In The System Of The Republic Of Indonesia By Constitution Of The Republic Of Indonesia 1945 - Baharudin Baharudin (Bandar Lampung University, 2015)
The results showed that(1) the design ofspecificareas/privilege is grantedtoprovincial-levelregionsandmunicipal levelarea/city. (2) Design ofgrantingthe status ofspecificity/privilegesinthe State of Indonesiais based ona varietyof reasons, namely(a) the grantingof special autonomyis moreemphasis onthe conditionsandthe real needs ofthe areaso that the necessaryimplementation ofthe authorityof a special nature, such as its positionasthe capital of theprovince ofthe Republic ofIndonesiaandas anautonomousregion, (b) theirresilienceandperseverancearesourcedfrom theview of lifewhich is based onIslamic Shariah; (c) the administration anddevelopmenthas notfullysatisfied the justice and social welfare, and has not fullysupported legal enforcement, andhas not yet shownrespect for human rights; (d) the historyandorigins ofthings, for exampleYogyakarta Sultanateandthe Duchy of Pakualamanwhichalready havetheir territory, government, andthe populationbeforethe birth ofthe Republic ofIndonesiaonAugust 17, 1945haveproved to beinstrumentalin maintaining, filling, andkeeping the integrity ofUnitary Republic ofIndonesia. (3) theoretically the establishment ofspecialautonomyis one wayor achoice madeby a countryto hold its togetherness(State unity).